Prevalence of hypertension and its associated risk factors among office employees working at BSNL and LIC offices of Bhopal city - Dubey, Manju; Choudhary, Yachana; Bhatia, Padma; Naik, G. P. (International Journal Of Community Medicine And Public Health, 2018)
Background: Hypertension is one of the leading causes of the global burden of disease. In India, the prevalence of hypertension is 33.8% in urban areas and 27.6% in rural areas. Hypertension is fairly common among white collar workers, owing to long working hours, sedentary lifestyle and due to lack of physical activity. This study was carried out among the office employees, who constitute one type of white collar workers. The aims and objectives of the study were to find out the prevalence of hypertension among office employees and to find out the various risk factors associated with hypertension among them. Methods: Descriptive cross-sectional study was carried out amongst 240 employees of two offices of Bhopal city from September to November 2016. Information regarding socio-demographic characteristics and various risk factors was collected. Measurement of blood pressure, height and weight of all participants were taken. Results: The prevalence of hypertension was found to be 53.33%, out of which 25.7% cases were newly diagnosed. Hypertension was positively associated with cigarette smoking, alcohol intake, adding extra salt to food. Conclusions: The prevalence of hypertension among office workers is alarmingly high (53.33% hypertensives and 25% prehypertensives) which calls for implementation of some interventional measures by the concerned authorities.